A Feminist Critique of Human Resource Development Research - Laura L. Bierma (Adult Education Research Conference, 1998)
This paper shares the results of a critique of human resource development (HRD) research, according to a feminist research framework. The paper offers a brief description of feminist research and challenges HRD researchers to be more critical of their practice.